Case of calcinosis cutis associated with Sjogren's syndrome - Keysha Gonzalez‐Ramos; Karishma Ramsubeik; Gurjit Kaeley (Clinical Case Reports, 2023)
Key Clinical Message Calcinosis cutis is a chronic condition involving skin and soft tissue deposition of calcium and phosphate. It is associated with several conditions including idiopathic, iatrogenic, malignant metastasis, calciphylaxis, and connective tissue diseases. The most common connective tissue diseases it is associated with include systemic sclerosis and dermatomyositis. We present a case image of a patient with Sjogren's syndrome and calcinosis cutis and its progression over time. The patient was optimized on her current treatment regimen to prevent further progression. Written informed consent was obtained from the patient to publish this report in accordance with the journal's patient consent policy.